Fontes e níveis de cobre na alimentação de leitões em creche e frangos de corte. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
This work aims to evaluate the effect of different levels and sources of copper on the performance of nursery piglets and broilers through meta-analysis. The criteria established for selecting articles were using various sources and levels of copper, diets for nursery pigs and broilers, performance results. Two databases were created from previously selected articles that evaluated different sources and levels of copper for nursery pigs and broilers. Fifty-nine articles published between 1990 and 2020 were compiled for nursery piglets, for a total of 931 treatments and 20,521 piglets. For broilers, 57 articles published between 1991 and 2020 were compiled, for a total of 96,606 birds in 717 treatments. Data analysis was explored by forest plot, heterogeneity, correlations, variance and covariance, and mixed models. The forest plot analysis indicates positive effects (P<0.05) of supplementation with inorganic and organic copper sources compared to basal treatments. However, the I2 indexes were >86.9%, indicating high heterogeneity for nursery piglets and broilers. The addition of copper at supra nutritional levels (>80 mg Cu/kg diet) increases the average daily gain by 3.4% and decreases feed conversion by 4.8% (P<0.05) in nursery pigs. Organic and inorganic copper sources improve weight gain and feed conversion compared to the basal treatment (1 to 15 mg Cu/kg diet (P<0.05). Mixed models indicate that bodyweight and mean age, and copper consumption influence the performance of nursery piglets. The Zn/Cu ratio was not significant in any model (P>0.05). In chickens, no variable was affected in the analysis of copper sources Broiler feed intake decreases (P>0.05) as levels above 81 mg Cu/kg in the diet are added. However, the weight gain and feed conversion of broilers are not altered by adding different sources and levels of copper to the diets. Mixed models indicate that the bodyweight of birds affects performance. The average intake of zinc and copper interfere with feed intake (P<0.05) without interfering with average daily gain and feed conversion. Organic and inorganic sources of copper and supra nutritional levels (> 81 mg Cu/kg diet) improve the performance of nursery piglets. Piglets fed diets containing organic or inorganic sources show similar performance. Broiler feed intake is influenced by live weight and copper and zinc intake. Supra nutritional levels (> 81 mg Cu/kg diet) in the diet reduce broiler feed intake without altering weight gain and feed conversion.
Keywords: Leitões em creche; frangos de corte; sulfato de cobre; cobre quelatado; meta- análise; Piglets; broilers; sulphated copper; chelated copper; meta-analysis; CNPQ::CIENCIAS AGRARIAS::ZOOTECNIA